Micellization Studies on Binary Mixture of Methionine with Polyoxyethylene (10) Cetyl Ether (Brij-56) and Polyoxyethylene (20) Cetyl Ether (Brij-58) - B. S. Bhadane; T. J. Patil (E-Journal of Chemistry)
The measurement of cloud point (CP) under the influence of additives provides an excellent tool for investigation of surfactant macromolecule interaction. The CP of pure surfactant polyoxyethylene (10) cetyl ether (Brij-56) and polyoxyethylene (20) cetyl ether (Brij-58) declined with increased [Bj-56] and [Bj-58]. The CP of mixed systems Brij-56/methionine and Brij-58/methionine shows same trends with increased [Met.]. This is mainly due to increased micelle concentrations. The influence of amino acid on the cloud point of Brij-56 and Brij-58 is a clear indication that the phenomenon of clouding is associated with the different micelles coalescing. The phase separation results from micelle-micelle interaction. Considering cloud point as threshold temperature of the solubility, the energetic of clouding process (ΔG0cl, ΔH0cl and ΔS0cl) have been evaluated using “Phase Separation Model" It is found that the overall clouding process is exothermic and ΔH0cl > TΔS0cl indicating that the process of clouding is guided by both enthalpy and entropy. This work supports the conjecture that the cloud point is critical phenomenon rather than the growth of micelles.